2022
DOI: 10.7717/peerj.13435
|View full text |Cite
|
Sign up to set email alerts
|

Land use/land cover changes in the central part of the Chitwan Annapurna Landscape, Nepal

Abstract: Background Land use/land cover assessment and monitoring of the land cover dynamics are essential to know the ecological, physical and anthropogenic processes in the landscape. Previous studies have indicated changes in the landscape of mid-hills of Nepal in the past few decades. But there is a lack of study in the Chitwan Annapurna Landscape; hence, this study was carried out to fill in study gap that existed in the area. Methods This study evaluates land use/land cover dynamics between 2000 to 2020 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…However, sandy area, water bodies and others land particularly built up area has been found increased during the study period in the park area (Figure 3). Similar type of study conducted in the Chitwan Annapurna Landscape area during 2000 to 2020 noticed an overall increase in Sal dominated forest, built up area, mixed forest and decreased in riverine forest, barren area, croplands and grasslands (Adhikari et al, 2022).…”
Section: Land Cover Changes Between 1994-2021 In Park Area Of Snnpsupporting
confidence: 60%
“…However, sandy area, water bodies and others land particularly built up area has been found increased during the study period in the park area (Figure 3). Similar type of study conducted in the Chitwan Annapurna Landscape area during 2000 to 2020 noticed an overall increase in Sal dominated forest, built up area, mixed forest and decreased in riverine forest, barren area, croplands and grasslands (Adhikari et al, 2022).…”
Section: Land Cover Changes Between 1994-2021 In Park Area Of Snnpsupporting
confidence: 60%
“…An analysis of the land use/land cover using Landsat imagery from 2020 revealed that the Chitwan area consists of grassland (1.73%), barren areas (1.76%), riverine forests (1.93%), water bodies (1.97%), developed areas (4.13%), Sal-dominated forests (15.4%), croplands (28.13%), and mixed forests (44.95%). Comparing land cover changes between 2000 and 2020, there was an overall increase in Sal-dominated forests (7.6%), developed areas (31.34%), and mixed forests (37.46%), and a decrease in riverine forests (11.29%), barren areas (20.03%), croplands (29.87%), and grasslands (49.71%) [ 31 , 32 ]. A significant portion of the forested land in the district is the Chitwan National Park, which is protected as a habitat for various wildlife and other ecological benefits, and attracts a large number of tourists [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The consistency of land cover classes at national, regional, and international levels is always different (Wang et al, 2020;Adhikari et al, 2022). In this study, we classified the land cover of Tikjda forest into three major classes (Table 1) based on the dominant soil present.…”
Section: Image-supervised Classificationmentioning
confidence: 99%
“…Spatiotemporal dynamics of forest areas over large extents is relevant for an improved understanding of forest ecology, for example, concerning species dynamics, and their role in ecosystem functions and services (Van Ewijk et al, 2014;Fassnacht et al, 2016;Mboga et al, 2020).Forest cover dynamics is largely evaluated around the world due to the increasing socioeconomic needs following the exponential increase of human population (Hassan et al, 2016;Zhu et al, 2021). Furthermore, understanding the dynamics of land cover and its impact on forest landscape functioning is critical for biodiversity conservation (García-Vega, Newbold, 2020), as it is necessary to understand the extent of the forest covers to identify the drivers and their effects on the ecological and anthropogenic processes (Adhikari et al, 2022). Nowadays, thanks to the combination of ecological history and remote sensing data, novel solutions are readily developed (Mboga et al, 2020;Solano et al, 2021).…”
Section: Introductionmentioning
confidence: 99%